The constant flux and constant sedimentation (CF:CS) 210Pb chronological method applied to determine sedimentation rates at Amazon River watershed, Brazil - Cardoso Nery, José Reinaldo (2022)
Activity profiles of excess 210Pb determined in three sediment cores from Amazon River mouth, Amapá State, Brazil, provide the evaluation of sedimentation rates, contributing to a better knowledge of the hydrological conditions. Chemical data on the sediments allowed calculation of the Geoaccumulation Index (Igeo) for each constituent analyzed. Significant direct relationships among Fe2O3 and major/minor constituents Al2O3 (r = 0.86), K2O (r = 0.94), MgO (r = 0.89), MnO (r = 0.92), BaO (r = 0.64), P2O5 (r = 0.62), and TiO2 (r = 0.54), inverse correlation between Fe2O3 and SiO2 (r = −0.93) and the direct correlation between SiO2 and LOI (loss on ignition) (r = 0.88) suggest competitive sorption of Si to Fe oxides and organic compounds. Igeo values between −3.75 and 0.22 for Si, Al, Na, K, Ca, Mg, Fe, Mn, Ti, P, S, Sr, Ba, Rb, Zn, Cr, Nb, Cu, Ni, As, V, Ga, Tb, Y, and Ce indicate practically unpolluted environments despite several mining activities in the Amazon basin and its vicinity. The apparent sediment mass accumulation rates between 0.5 and 2.4 gcm−2yr−1 are compatible with the results of others studies. The 210Pb activity at one sampling point (P1) exhibited an abrupt fluctuation, similar to findings from previous studies held at the northern channel of the Amazon River discharge. On the other hand, in two sediment profiles (P2 and P3), the excess 210Pb activity data validate the use of the CF:CS method, yielding unique straight lines and increasing the sedimentation rates database.